2017
DOI: 10.1186/s12864-017-3737-z
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome sequencing identifies missense mutation in MTBP in Shar-Pei affected with Autoinflammatory Disease (SPAID)

Abstract: BackgroundAutoinflammatory diseases in dogs are characterized by complex disease processes with varying clinical signs. In Shar-Pei, signs of inflammation including fever and arthritis are known to be related with a breed-specific predisposition for Shar-Pei Autoinflammatory Disease (SPAID).ResultsClinical and histopathological examinations of two severely SPAID-affected Shar-Pei revealed signs of inflammation including fever, arthritis, and perivascular and diffuse dermatitis in both dogs. A multifocal accumu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 52 publications
0
24
0
Order By: Relevance
“…The dataset designed for this study is represented by 154 samples (Table S2), including one Andean fox (Lycalopex culpaeus) 45 , three golden jackals (Canis aureus) 13,14,46 , four coyotes (Canis latrans) 46,47 , four African golden wolf (Canis lupaster) 46,48,49 , one Ethiopian wolf (Canis simensis) 46 , 62 modern wolves (Canis lupus) from Eurasia and North America 13,14,22,46,[50][51][52][53] , 45 modern dogs 12,14,45,[51][52][53][54][55][56][57][58][59] (see Table S2 for more information), 24 ancient dogs (Canis lupus familiaris) 32,51,[60][61][62][63] , five Pleistocene wolves 15,51 and five newly sequenced Sicilian wolves (Canis lupus cristaldii). In this dataset 33 modern wolves and three Cirneco dogs were newly sequenced as part of this study.…”
Section: Datasetmentioning
confidence: 99%
“…The dataset designed for this study is represented by 154 samples (Table S2), including one Andean fox (Lycalopex culpaeus) 45 , three golden jackals (Canis aureus) 13,14,46 , four coyotes (Canis latrans) 46,47 , four African golden wolf (Canis lupaster) 46,48,49 , one Ethiopian wolf (Canis simensis) 46 , 62 modern wolves (Canis lupus) from Eurasia and North America 13,14,22,46,[50][51][52][53] , 45 modern dogs 12,14,45,[51][52][53][54][55][56][57][58][59] (see Table S2 for more information), 24 ancient dogs (Canis lupus familiaris) 32,51,[60][61][62][63] , five Pleistocene wolves 15,51 and five newly sequenced Sicilian wolves (Canis lupus cristaldii). In this dataset 33 modern wolves and three Cirneco dogs were newly sequenced as part of this study.…”
Section: Datasetmentioning
confidence: 99%
“…Chronic inflammatory conditions often precede reactive amyloidosis, and a hereditary autoinflammatory disease has been suggested in the development of amyloidosis in Chinese Shar-Pei. 1,8 Abnormal secretion of interleukin-1β in autoinflammatory disease leads to the hepatic induction of serum amyloid A. 7 This underlying immune dysregulation may play a role in the progression and severity of reactive amyloidosis.…”
Section: Discussionmentioning
confidence: 99%
“…7 Genetic analysis of this breed identified 1 primary risk locus; however, a modifier locus was suggested. 7,8 Proteinuric nephropathy and renal amyloidosis affecting Bracchi Italiani have been recognized (R Propernick, Bracco Italiano Club of America, email, December 18, 2011) but was not mentioned in previous reports. [4][5][6] Therefore, the objective of the study reported here was to characterize the signalment, clinical signs, clinical pathological and histologic findings, and outcome for 8 related adult purebred Bracchi Italiani with proteinuric kidney disease.…”
Section: Conclusion and Clinical Relevancementioning
confidence: 99%
“…The dataset used for this study includes 74 canid whole-genomes: one Andean fox ( Lycalopex culpaeus ) (Auton et al 2013), two coyotes ( Canis latrans ) (Gopalakrishnan et al 2018; vonHoldt et al 2022), 51 wolves ( Canis lupus ) (Hennelly et al 2021; Ramos-Madrigal et al 2021; Niemann et al 2021; Sinding et al 2020; Sinding et al 2018; Fan et al 2016; vonHoldt et al 2016; Wang et al 2016; Wang et al 2013; Freedman et al 2014; Zhang et al 2014), and 20 dogs. (Sinding et al 2020; Kolicheski et al 2017; Marchant et al 2017; Metzger et al 2017; Marsden et al 2016; Wang et al 2016; Decker et al 2015; Freedman et al 2014; Auton et al 2013; Kim et al 2012; Lindblad-Toh et al 2005) Among the wolf samples, 40 are reference genomes mainly representing Asian populations; five correspond to Pleistocene wolves from Siberia, nine correspond to wolves resequenced for this study representing wolf populations in Asia, and two are the Korean wolves: a modern captive wolf (PZW) from the Seoul Grand Park in South Korea, and a 20th century stuffed Korean wolf (HKW) from the Kyungpook University Museum. Finally, all dog genomes included here are already published and they were selected to mainly represent Asian breeds (Table S2).…”
Section: Methodsmentioning
confidence: 99%